Back Cover: Dimers of Nineteen‐Electron Sandwich Compounds: Crystal and Electronic Structures, and Comparison of Reducing Strengths (Chem. Eur. J. 47/2014). Issue 47 (17th November 2014) - Mohapatra, Swagat K.; Fonari, Alexandr; Risko, Chad; Yesudas, Kada; Moudgil, Karttikay; Delcamp, Jared H.; Timofeeva, Tatiana V.; Brédas, Jean‐Luc; Marder, Seth R.; Barlow, Stephen
<x xml:space="preserve">Abstract</x> Dissociation energies, ΔUdiss, of dimeric organometallic n‐dopants affect the thermodynamics and kinetics of their redox reactions. Although the bond lengths in dimers of organic radicals decrease with increasing ΔUdiss, this is not the case for the present dimers; instead, trends in stability of ΔUdiss correlate with those in the stability of the 19‐elecron monomers. The HOMOs and X‐ray structures of [RuCp*(C6H3Et3)]2 and [FeCp*(C6H6)]2 are shown; DFT calculations indicated a significantly larger ΔUdiss for the former, yet X‐ray (and DFT) showed a slightly longer bond. For more details, see the Full Paper by S. Barlow et al. on page 15385 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>